A multi-approaches examination of toxicological effects of a naturally-occurring plant alkaloid veratridine, and the synthetic type II pyrethroid lambda-cyhalothrin on honey bees - Aklesso Kadala; Mercédès Charreton; Michel Pélissier; Jérôme Mutterer; Mohamed Chahine; Pierre Charnet; Claude Collet (Environmental Toxicology and Pharmacology, 2026)

Knockout of the antiviral genes mx1 or mx3 modulates the expression of paralogous genes in a salmonid cell line - Lise Chaumont; Mathilde Peruzzi; François Huetz; Claudine Raffy; Jérôme Le Hir; Jules Minke; Jo-Ann C. Leong; Pierre Boudinot; Bertrand Collet (Fish & Shellfish Immunology, 2026)

Toll-like Receptor 3 is Required for Sensing Extracellular Double Stranded RNA in Salmonid Cells - Bertrand Collet; Catherine Collins; Mathilde Peruzzi; Justine Catherine-Mezeray; Stephanie DeWitte-Orr; Alexander Rebl; Pierre Boudinot (Marine Biotechnology, 2026)

Limited human mobility during the Neolithic period in the Meuse and Mons basin in Belgium: multi-element isotopic analysis - IJk van Hattum; Marta Costas-Rodríguez; Kasper Hobin; Prudence Robert; Frank Vanhaecke; Elliot Van Maldegem; Hélène Collet; Pierre Cattelain; Michel Toussaint; Hans Vandendriessche; Samuel Bodé; Pascal Boeckx; et al. (Archaeological and Anthropological Sciences, 2026)
While the introduction of the Neolithic way of life in central Belgium around 5300 BCE is well-documented, the provenance and mobility patterns of Middle to Final Neolithic groups in southern Belgium (Wallonia) remain unclear. This work presents the first multi-element isotopic (strontium, 87 Sr/ 86 Sr; oxygen, δ 18 O; carbon, δ 13 C) data from prehistoric human dental enamel from the region. The study includes a total of 29 individuals, coming from karstic caves in the Meuse basin, the mining complex of Spiennes, and the megalithic tomb of Wéris II. The study also explores the variability of bioavailable strontium ratios in the geologically heterogeneous Meuse basin using modern plants. The analysis of multi-element isotopic data reveals high δ 18 O values and diverse 87 Sr/ 86 Sr ratios. The findings suggest that these individuals likely originated from or spent their childhood in present-day Belgium. Furthermore, the study highlights limited mobility during the Final Neolithic period, characterized by a combination of local residency and potential short-distance mobility or post-mortem movements. Overall, this study provides the first δ 18 O values from ancient human remains in the region and reshapes our understanding of human mobility during the Neolithic in present-day Belgium.

Multi-pollutant contribution of wood heating to emissions, concentrations and population exposure during winter time down to the street levels - Lya Lugon; Charles Kimmerlin; Youngseob Kim; Pierre Pousset; Jérémie Achille; Fabrice Joly; Florian Couvidat; Serge Collet; Benjamin Cuniasse; Matteo Redaelli; Karine Sartelet (Journal of Hazardous Materials, 2026)

Functionality of duplicated cd9 paralogous antiviral genes in salmonids - Max Charles Vallarino; Victoria A. Sleight; Bertrand Collet; Pierre Boudinot; Samuel A.M. Martin (Fish & Shellfish Immunology, 2025)

Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark; Valentin Thomas; Richard S. Taylor; Mathieu Charles; Audrey Laurent; Isabelle Schwartz-Cornil; Bertrand Collet; Delphine Lallias; Daniel J. Macqueen; Samuel A.M. Martin; Pierre Boudinot (Fish & Shellfish Immunology, 2025)

Disruption of Myd88 in a salmonid epithelioid cell line reveals its contribution to bacterial detection and immune response - Alexander Rebl; Mathilde Peruzzi; Catherine Collins; Niccolò Vendramin; Pierre Boudinot; Niels Lorenzen; Bertrand Collet (Cell and Tissue Research, 2025)

Innovative Pathways for the use of Excavation Materials in the Frame of the Future Circular Collider Project - Elisabeth Hauzinger; Luisa Ulrici; Johannes Gutleber; Robert Galler; Daniel Schneider; Maximilian Haas; Michael Benedikt; Mathieu Pillet; Jérémy Voiron; Pierre Boillon; Agathe Denot; Julie Paciello; et al. (Circular Economy and Sustainability, 2025)
Based a recommendation of the European strategy of particle physics of 2020 due to the great research success of the last decade CERN is planning a new circular collider with a circumference of approximately 91 km. To start construction in the middle 2030s a feasibility study is underway which includes scientific and financial components as well as territorial aspects such as geology, environment, technical infrastructure and civil engineering. One important factor is the management of the approximately 8 Mio. m3 of excavation materials, which consists mostly of molassic sediments of the Geneva Basin. In order to ensure that as much of the material as possible is put to high quality use in accordance with local regulations, the international contest “Mining the Future ® ” was launched. For this task geotechnical, mineralogical and geochemical tests were carried out on a large number of samples from across the study area. Based on the results, various utilization options were designed, which are primarily oriented towards alternative building materials with a low carbon footprint as well as agricultural use. The resulting concept of these sustainable strategies not only has a positive impact on the construction industry, but also play a major socio-economic role, as they improve social acceptance as well as responsibility in relation to large-scale projects.

Unravelling impacts of the insecticide deltamethrin on neuronal sodium channels in honey bees: Molecular insights and behavioural outcomes - Aklesso Kadala; Mahira Kaabeche; Mercédès Charreton; Jérôme Mutterer; Michel Pélissier; Thierry Cens; Matthieu Rousset; Mohamed Chahine; Pierre Charnet; Claude Collet (Chemosphere, 2024)

Cardiac electrical and functional activity following an outdoor cold-water swimming event - Victorien Faivre-Rampant; Corentin Hingrand; A. Mezanger; Eric Saloux; Pierre Ollitrault; Simon Alvado; Hervé Normand; Igor B. Mekjavic; Thibaud Collet; Benoit Mauvieux; Joffrey Drigny; Amir Hodzic (Journal of Thermal Biology, 2024)

Combining economics and psychology: Does CO 2 framing strengthen pro-environmental behaviors? - Charles Collet; Pascal Gastineau; Benoît Chèze; Pierre-Alexandre Mahieu; Frédéric Martinez (Ecological Economics, 2023)

Prioritizing regionalization to enhance interpretation in consequential life cycle assessment: application to alternative transportation scenarios using partial equilibrium economic modeling - Laure Patouillard; Daphné Lorne; Pierre Collet; Cécile Bulle; Manuele Margni (The International Journal of Life Cycle Assessment, 2020)

Back to the future: dynamic full carbon accounting applied to prospective bioenergy scenarios - Ariane Albers; Pierre Collet; Anthony Benoist; Arnaud Hélias (The International Journal of Life Cycle Assessment, 2020)

Prioritizing regionalization efforts in life cycle assessment through global sensitivity analysis: a sector meta-analysis based on ecoinvent v3 - Laure Patouillard; Pierre Collet; Pascal Lesage; Pablo Tirado Seco; Cécile Bulle; Manuele Margni (The International Journal of Life Cycle Assessment, 2019)

Development of an Efficient Genome Editing Method by CRISPR/Cas9 in a Fish Cell Line - Carola E. Dehler; Pierre Boudinot; Samuel A. M. Martin; Bertrand Collet (Marine Biotechnology, 2016)
CRISPR/Cas9 system has been used widely in animals and plants to direct mutagenesis. To date, no such method exists for fish somatic cell lines. We describe an efficient procedure for genome editing in the Chinook salmon Oncorhynchus tshawytscha CHSE. This cell line was genetically modified to firstly overexpress a monomeric form of EGFP (cell line CHSE-E Geneticin resistant) and additionally to overexpress nCas9n, a nuclear version of Cas9 (cell line CHSE-EC, Hygromycin and Geneticin resistant). A pre-validated sgRNA was produced in vitro and used to transfect CHSE-EC cells. The EGFP gene was disrupted in 34.6 % of cells, as estimated by FACS and microscopy. The targeted locus was characterised by PCR amplification, cloning and sequencing of PCR products; inactivation of the EGFP gene by deletions in the expected site was validated in 25 % of clones. This method opens perspectives for functional genomic studies compatible with high-throughput screening.

Genetic and platelet function testing of antiplatelet therapy for percutaneous coronary intervention: the ARCTIC-GENE study - Jean-Philippe Collet; Jean-Sébastien Hulot; Thomas Cuisset; Grégoire Rangé; Guillaume Cayla; Eric Van Belle; Simon Elhadad; Hélène Rousseau; Pierre Sabouret; Stephen A. O’Connor; Jérémie Abtan; Mathieu Kerneis; et al. (European Journal of Clinical Pharmacology, 2015)

How to take time into account in the inventory step: a selective introduction based on sensitivity analysis - Pierre Collet; Laurent Lardon; Jean-Philippe Steyer; Arnaud Hélias (The International Journal of Life Cycle Assessment, 2014)

Characterization of the first honeybee Ca2+ channel subunit reveals two novel species- and splicing-specific modes of regulation of channel inactivation - Thierry Cens; Matthieu Rousset; Claude Collet; Valérie Raymond; Fabien Démares; Annabelle Quintavalle; Michel Bellis; Yves Le Conte; Mohamed Chahine; Pierre Charnet (Pflügers Archiv - European Journal of Physiology, 2013)